Primary small cell carcinoma of urinary bladder (Journal of Pathology of Nepal, 2015)
Primary pure small cell carcinoma of the urinary bladder is an extremely rare and highly aggressive tumor with an average five-year survival rate of less than 10% as cited by multiple case reports. It accounts for about 0.5-1% of all bladder tumors. We present the case of an 87-years-old man; smoker hospitalized in the Department of Urology, from the Institute of Medicine, Kathmandu for intermittent painless hematuria. Ultrasonography showed a sessile tumoral growth. Transurethral resection of the tumor mass was performed and tissue fragments were sent to the pathologic lab to establish the histologic type, the degree of differentiation and invasion. Fragments of the tumor were fixed in 10% formaldehyde, paraffin embedded and processed as standard technique; the sections were stained with H and E and immunohistochemically with NSE and Cytokeratin.  A diagnosis of small cell carcinoma was established. Because of aggressive behavior and distinct treatment, the pathologist should watch out for the presence of small cell carcinoma component.